The prevalence of prescribing medications associated with geriatric syndromes among discharged elderly patients - Akkawi, Muhammad Eid; Taufek, Nor Hidayah (2020)
Introduction: A geriatric syndrome is a group of signs and symptoms that occur in older people and do not fit into a discrete disease. Several medications were reported to be associated with the incidence of geriatric syndromes. Objective: The objective of this study was to investigate the prevalence and pattern of medications associated with geriatric syndromes (MAGSs) among the discharged elderly patients (≥65 years old). Materials and Methods: This is a cross-sectional study that was conducted at a Malaysian teaching hospital from October to December 2018. The discharge medications of geriatric patients were reviewed to identify MAGSs using Beers criteria, Lexicomp drug information handbook, and the United States Food and Drug Administration (USFDA) drug inserts. Chi-square test was used to compare MAGS prescribed between categories. Spearman’s rank-order correlation was used to test the correlation between the presence of MAGS and the number of discharge medications. A binomial logistic regression was applied to determine the predictors of prescribing MAGSs. Results: A total of 400 patients (mean ± standard deviation [SD] age, 72.0 ± 5.0 years) were included, and 45.3% of them were females. The most common diseases were hypertension followed by diabetes mellitus. The mean ± SD number of discharge medications per patient was 4.2 ± 2.5. The MAGSs were prescribed in 51.7% of the patients, and 54 patients were discharged with more than one MAGSs. The most commonly prescribed MAGSs were opioid analgesics, vasodilators, and β-blockers, which are associated with falls, depression, and delirium. Polypharmacy was found in 138 patients, and it was significantly associated with the presence of MAGSs (P < 0.001). No significant differences were found in prescribing MAGSs based on the patients’ gender, race, and age. Conclusion: The prescribing of MAGSs occurred in half of the discharged elderly patients. Physicians should be aware of the medications that are associated with special side effects in the elderly patients, and should switch to safer alternatives when possible.